Neuroprotective and intraocular pressure lowering effects of dual-functional memantine nitrate MN-08 on the experimental models of glaucoma - Huihui Hu; Liangmiao Wu; Xiaodie Hu; Minghua Wang; Yewei Sun; Gaoxiao Zhang; Yuqiang Wang; Peng Yi; Zaijun Zhang (Scientific Reports)
Abstract Glaucoma stands out as the primary cause of permanent blindness worldwide, marked by elevated intraocular pressure (IOP) and the deterioration of retinal ganglion cells (RGCs) within the optic nerve. This study aimed to investigate the therapeutic efficacy of MN-08, a novel memantine nitrate derivative, in experimental models of glaucoma. In the rat model of retinal ischemia–reperfusion injury, MN-08 prevented the reduction in retinal ganglion cell complex (GCC) thickness and RGC loss. Meanwhile, MN-08 reduced the protein levels of cleaved-caspase-3, caspase-3, and Bax, while increasing the expression of Bcl-2 compared to the model group, indicating that MN-08 exerts an inhibitory effect on the apoptosis of RGCs. Furthermore, MN-08 lowered IOP in the transient ocular hypertension and glaucoma rabbit models. MN-08 significantly increased cGMP levels in human trabecular meshwork cells (HTMCs). Elevation of cGMP induced by MN-08 was eliminated by ODQ. Moreover, MN-08 attenuated the protein levels of MLCK and p-MLC-2 in HTMCs induced by endothelin-1. Additionally, MN-08 exhibited favorable distribution profiles and pharmacokinetic parameters in normal rabbit ocular tissues following topical instillation. These findings indicate that MN-08 could antagonize NMDA receptors to protect RGCs and release NO to relax TM for the treatment of glaucoma.